A poplar R2R3-MYB transcription factor, PtrMYB152, is involved in regulation of lignin biosynthesis during secondary cell wall formation - Chaofeng Li; Xianqiang Wang; Wanxiang Lu; Rui Liu; Qiaoyan Tian; Yiming Sun; Keming Luo (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

piggyBac transposon-derived targeting shRNA interference against the Bombyx mori nucleopolyhedrovirus (BmNPV) - Fang Zhou; Rui-ting Chen; Yan Lu; Shuang Liang; Mei-xian Wang; Yun-gen Miao (Molecular Biology Reports, 2014)

Transcriptome profiling of biliary atresia from new born infants by deep sequencing - Jie Xiao; Su-yun Xia; Yun Xia; Qiang Xia; Xiang-rui Wang (Molecular Biology Reports, 2014)

Identification and validation of suitable reference genes for RT-qPCR analysis in mouse testis development - Zu-Kang Gong; Shuang-Jie Wang; Yong-Qi Huang; Rui-Qiang Zhao; Qi-Fang Zhu; Wen-Zhen Lin (Molecular Genetics and Genomics, 2014)

Upregulation of HIF-1α Via Activation of ERK and PI3K Pathway Mediated Protective Response to Microwave-Induced Mitochondrial Injury in Neuron-Like Cells - Li Zhao; Yue-Feng Yang; Ya-Bing Gao; Shui-Ming Wang; Li-Feng Wang; Hong-Yan Zuo; Ji Dong; Xin-Ping Xu; Zhen-Tao Su; Hong-Mei Zhou; Ling-Ling Zhu; Rui-Yun Peng (Molecular Neurobiology, 2014)

Hyperacetylation of Histone H3K9 Involved in the Promotion of Abnormally High Transcription of the gdnf Gene in Glioma Cells - Zheng-Quan Yu; Bao-Le Zhang; Hai-Bo Ni; Ze-Hao Liu; Jian-Cun Wang; Qing-Xian Ren; Jian-Bing Mo; Ye Xiong; Rui-Qin Yao; Dian-Shuai Gao (Molecular Neurobiology, 2014)

Optimal intervention time of vagal stimulation attenuating myocardial ischemia/reperfusion injury in rats - Qiang Wang; Rui-Ping Li; Fu-Shan Xue; Shi-Yu Wang; Xin-Long Cui; Yi Cheng; Gao-Pu Liu; Xu Liao (Inflammation Research, 2014)

Investigation on Etiology of Hepatic Venous Obstruction Budd-Chiari Syndrome - Zhi-Long Tian; Gao-Lei Jia; Hai-Lin Xi; Su Feng; Xiao-Kai Wang; Rui Li (Cell Biochemistry and Biophysics, 2014)

MTA1—a stress response protein: a master regulator of gene expression and cancer cell behavior - Rui-An Wang (Cancer and Metastasis Reviews, 2014)

Structures and antiviral activities of butyrolactone derivatives isolated from Aspergillus terreus MXH-23 - Xinhua Ma; Tianjiao Zhu; Qianqun Gu; Rui Xi; Wei Wang; Dehai Li (Journal of Ocean University of China, 2014)

An overview of passive and active dust detection methods using satellite measurements - Bin Chen; Peng Zhang; Beidou Zhang; Rui Jia; Zhijuan Zhang; Tianhe Wang; Tian Zhou (Journal of Meteorological Research, 2014)

Genomewide identification and expression analysis of the ARF gene family in apple - XIAO-CUI LUO; MEI-HONG SUN; RUI-RUI XU; HUAI-RUI SHU; JIA-WEI WANG; SHI-ZHONG ZHANG (Journal of Genetics, 2014)

Association of microRNA-3144 variant with the susceptibility to hepatocellular carcinoma - Jun Zhang; Rui Wang; Min Cai; Shunji Yu; Yanyun Ma; Weihong Xu; Chunfang Gao; Jiucun Wang; Lifang Hou; Yi Liu; Jie Liu (Genes & Genomics, 2014)

Research on hydrochemical spatio-temporal characteristics of groundwater quality of different aquifer systems in Songhua River Basin, eastern Songnen Plain, Northeast China - Rui Wang; Jian-Min Bian; Yue Gao (Arabian Journal of Geosciences, 2014)

Semicarbazide – from state-of-the-art analytical methods and exposure to toxicity: a review - Wen-Rui Tian; Ya-Xin Sang; Xiang-Hong Wang (Food Additives & Contaminants: Part A, 2014)

Antibacterial activities of nemonoxacin against clinical isolates of Staphylococcus aureus: an in vitro comparison with three fluoroquinolones - Zhaoxia Li; Youning Liu; Rui Wang; Aimin Li (World Journal of Microbiology and Biotechnology, 2014)

A thinned lithosphere beneath coastal area of southeastern China as evidenced by seismic receiver functions - Zhuo Ye; QiuSheng Li; Rui Gao; HongShuang Zhang; RiZheng He; HaiYan Wang; WenHui Li (Science China Earth Sciences, 2014)

Rheological Characteristics of Weak Rock Mass and Effects on the Long-Term Stability of Slopes - Tianhong Yang; Tao Xu; Hongyuan Liu; Chunming Zhang; Shanyong Wang; Yongqin Rui; Li Shen (Rock Mechanics and Rock Engineering, 2014)

Involvement of calcium-sensing receptors in hypoxia-induced vascular remodeling and pulmonary hypertension by promoting phenotypic modulation of small pulmonary arteries - Xue Peng; Hong-Xia Li; Hong-Jiang Shao; Guang-Wei Li; Jian Sun; Yu-Hui Xi; Hong-Zhu Li; Xin-Yan Wang; Li-Na Wang; Shu-Zhi Bai; Wei-Hua Zhang; Li Zhang; et al. (Molecular and Cellular Biochemistry, 2014)

Impact of diurnal temperature range on human health: a systematic review - Jian Cheng; Zhiwei Xu; Rui Zhu; Xu Wang; Liu Jin; Jian Song; Hong Su (International Journal of Biometeorology, 2014)

PAHs in PM2.5 in Zhengzhou: concentration, carcinogenic risk analysis, and source apportionment - Jia Wang; Ning Bo Geng; Yi Fei Xu; Wen Ding Zhang; Xiao Yan Tang; Rui Qin Zhang (Environmental Monitoring and Assessment, 2014)

Snail regulated by PKC/GSK-3β pathway is crucial for EGF-induced epithelial-mesenchymal transition (EMT) of cancer cells - Zong-cai Liu; Xiao-hui Chen; Hai-xing Song; Hong-sheng Wang; Ge Zhang; Hao Wang; Dan-yang Chen; Rui Fang; Hao Liu; Shao-hui Cai; Jun Du (Cell and Tissue Research, 2014)

How UV photolysis accelerates the biodegradation and mineralization of sulfadiazine (SD) - Shihui Pan; Ning Yan; Xinyue Liu; Wenbing Wang; Yongming Zhang; Rui Liu; Bruce E. Rittmann (Biodegradation, 2014)

The influence of Caragana korshinskii shrub on soil and hydrological properties in a revegetation-stabilized desert ecosystem - Yan-Xia Pan; Xin-Ping Wang; Xin-Rong Li; Ya-Feng Zhang; Rui Hu; Hao Zhang (Hydrological Sciences Journal, 2014)

Two new cadinane-type sesquiterpenes from the Chinese liverwort Frullania serrata - Rui-Juan Li; Rong-Xiu Zhu; Yu Zhao; Susan L. Morris-Natschke; Chin-Ho Chen; Song Wang; Jiao-Zhen Zhang; Jin-Chuan Zhou; Hong-Xiang Lou; Kuo-Hsiung Lee (Natural Product Research, 2014)

RETRACTED ARTICLE: Meta-analysis of the relationship between single nucleotide polymorphism rs72689236 of caspase-3 and Kawasaki disease - Yanlin Xing; Hong Wang; Xiaomei Liu; Xianyi Yu; Rui Chen; Ce Wang; Xuexin Yu; Le Sun (Molecular Biology Reports, 2014)

Needle-free injection of insulin powder: delivery efficiency and skin irritation assessment - Chun-yu Li; Zhe-wei Wang; Can Tu; Jia-bo Wang; Bing-qian Jiang; Qi Li; Ling-na Zeng; Zhi-jie Ma; Ping Zhang; Yan-ling Zhao; Ya-ming Zhang; Dan Yan; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

ORF005L from infectious spleen and kidney necrosis virus is located in the inner mitochondrial membrane and induces apoptosis - Rui Wang; Yang Yi; Lihong Liu; Yanghong Lu; Shaoping Weng; Jianguo He; Xiaopeng Xu (Virus Genes, 2014)

A new algorithm for fine acquisition of GPS carrier frequency - Kedong Wang; Rui Jiang; Yong Li; Ning Zhang (GPS Solutions, 2014)

Zircon U–Pb geochronology and geochemistry of the Maoliger quartz monzodiorites, Inner Mongolia, China: implications for Carboniferous arc magmatism and closure of the Palaeo-Asian Ocean - Li-Min Wang; Xiao-Guo Chi; Zhi Zhao; Wei Sun; Rui Zhang; Shi-Yu Pan; Jing-Yu Quan (International Geology Review, 2014)

Lack of association between the G+2044A polymorphism of interleukin-13 gene and chronic obstructive pulmonary disease: a meta-analysis - Lian Duan; Rui Liang; Zhendong Wang; Lei Lei; Lianhong Jin; Jingling Shen; Shoude Jin (Molecular Biology Reports, 2014)

Toxic effects of sodium fluoride on cell proliferation and apoptosis of Leydig cells from young mice - Guo hua Song; Rui Li Wang; Zhao Yang Chen; Bin Zhang; Hai Long Wang; Mao Lin Liu; Ji Ping Gao; Xiao Yan Yan (Journal of Physiology and Biochemistry, 2014)

Simultaneous inversion of petrophysical parameters based on geostatistical a priori information - Xing-Yao Yin; Rui-Ying Sun; Bao-Li Wang; Guang-Zhi Zhang (Applied Geophysics, 2014)

Phylogenetic relationships between Leymus and related diploid Triticeae species revealed by ISSR markers - Guo-Ye Guo; Rui-Wu Yang; Chun-Bang Ding; Li Zhang; Yong-Hong Zhou; Fang Chen; Sheng-Hua Wang (Biologia, 2014)

Molecular cloning and expression analysis of mannose receptor in blunt snout bream (Megalobrama amblycephala) - Xiaoling Liu; Xiaocheng Tang; Li Wang; Jie Li; Hong Wang; Shun Wei; Rui Fang; Wei Ji; Gailing Yuan; Nan Chen; Zemao Gu; Xueqin Liu; et al. (Molecular Biology Reports, 2014)

RETRACTED ARTICLE: Uncovering the pathogenesis and identifying novel targets of pancreatic cancer using bioinformatics approach - Li-Li Zhao; Tong Zhang; Li-Wei Zhuang; Bing-Zhu Yan; Rui-Feng Wang; Bing-Rong Liu (Molecular Biology Reports, 2014)

Characterization and expression profiles of MaACS and MaACO genes from mulberry (Morus alba L.) - Chang-ying Liu; Rui-hua Lü; Jun Li; Ai-chun Zhao; Xi-ling Wang; Umuhoza Diane; Xiao-hong Wang; Chuan-hong Wang; Ya-sheng Yu; Shu-mei Han; Cheng Lu; Mao-de Yu (Journal of Zhejiang University-SCIENCE B, 2014)

Protective Effects of Selenium on Mercury Induced Immunotoxic Effects in Mice by Way of Concurrent Drinking Water Exposure - Xuan Li; Daqiang Yin; Jiang Li; Rui Wang (Archives of Environmental Contamination and Toxicology, 2014)

Airborne fine particulate matter induces multiple cell death pathways in human lung epithelial cells - Xiaobei Deng; Fang Zhang; Lijuan Wang; Wei Rui; Fang Long; Yong Zhao; Deliang Chen; Wenjun Ding (Apoptosis, 2014)

Modeling Carbon Fluxes Using Multi-Temporal MODIS Imagery and CO2 Eddy Flux Tower Data in Zoige Alpine Wetland, South-West China - Xiaoming Kang; Yanfen Wang; Huai Chen; Jianqing Tian; Xiaoyong Cui; Yichao Rui; Lei Zhong; Paul Kardol; Yanbin Hao; Xiangming Xiao (Wetlands, 2014)

Anti-stress properties and two HSP70s mRNA expressions of blunt snout bream (Megalobrama amblycephala) fed with all-plant-based diet - Wei Deng; Yuhua Zhao; Weimin Wang; Yasmeen Gul; Junming Cao; Yanhua Huang; Guangcheng Sheng; Zhujin Ding; Rui Du (Fish Physiology and Biochemistry, 2014)

Purification and photodynamic bioactivity of phycoerythrin and phycocyanin from Porphyra yezoensis Ueda - Chuner Cai; Yuan Wang; Chunxia Li; Ziye Guo; Rui Jia; Weining Wu; Yan Hu; Peimin He (Journal of Ocean University of China, 2014)

Shoot regeneration and cryopreservation of shoot tips of apple (Malus) by encapsulation–dehydration - Bai-Quan Li; Chao-Hong Feng; Ling-Yun Hu; Min-Rui Wang; Long Chen; Qiao-Chun Wang (In Vitro Cellular & Developmental Biology - Plant, 2014)

Isolation and characterization of twenty-three polymorphic microsatellite loci in Schizothorax macropogon - Xiang-Zhao Guo; Gui-Rong Zhang; Ruo-Jin Yan; Wei Ji; Rui-Bin Yang; Kai-Jian Wei; Deng-Qiang Wang (Conservation Genetics Resources, 2014)

Expression and roles of As-NUPR1 protein from Artemia sinica during embryo development and in response to salinity stress - Rui Zhang; Feng Yao; Cheng Cheng; Yifei Chen; Ying Lv; Zengrong Li; Na Zhao; Ting Wang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

Down-regulated Six2 by knockdown of neurofibromin results in apoptosis of metanephric mesenchyme cells in vitro - Puhui Zhou; Tielin Chen; Yin Fang; Honglian Wang; Mi Li; Pengpeng Ma; Lu He; Qianyin Li; Tianming Liu; Xianggui Yang; Fang Nie; Xiaoyan Wang; et al. (Molecular and Cellular Biochemistry, 2014)

DNA Binding Property and Antitumor Evaluation of Xanthone with Dimethylamine Side Chain - Rui Shen; Weihua Wang; Gengliang Yang (Journal of Fluorescence, 2014)

Time-dependent damage constitutive model for the marble in the Jinping II hydropower station in China - Bing-Rui Chen; Xiao-Jun Zhao; Xia-Ting Feng; Hong-Bo Zhao; Shan-Yong Wang (Bulletin of Engineering Geology and the Environment, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Tropomyosin-related kinase B promotes distant metastasis of colorectal cancer through protein kinase B-mediated anoikis suppression and correlates with poor prognosis - Meng Fan; Jianyong Sun; Wei Wang; Jing Fan; Lei Wang; Xiang Zhang; Angang Yang; Weizhong Wang; Rui Zhang; Jipeng Li (Apoptosis, 2014)

Discriminative host sanctions in a fig–wasp mutualism - Rui-Wu Wang; Derek W. Dunn; Bao Fa Sun (Ecology, 2014)
In some mutualisms, cooperation in symbionts is promoted by hosts sanctioning “cheats,” who obtain benefits but fail to reciprocate. In fig–wasp mutualisms, agaonid wasps pollinate the trees ( Ficus spp.), but are also exploitative by using some flowers as larval food. Ficus can sanction cheats that fail to pollinate by aborting some un‐pollinated figs. However, in those un‐pollinated figs retained by trees, cheats successfully reproduce. When this occurs, wasp broods are reduced, suggesting sanctions increase offspring mortality within un‐pollinated figs. We investigated sanction mechanisms of abortion and larval mortality against wasp cheats in the monoecious Ficus racemosa by introducing into figs 1, 3, 5, 7, or 9 female wasps (foundresses) that were either all pollen‐laden (P+) or all pollen‐free (P−). The abortion rates of P− figs were highest (∼60%) when single foundresses were present. Abortion declined with increased foundresses and ceased with seven or more wasps present, irrespective of pollination. In un‐aborted figs, wasp fitness (mean offspring per foundress) declined as foundress number increased, especially in P− figs. Reduced broods in P− figs resulted from increased larval mortality of female offspring as foundress number increased, resulting in more male‐biased sex ratios. Overall sanctions estimated from both abortion rates and reduced offspring production strengthened as the number of cheats increased. In a second experiment, we decoupled pollination from wasp oviposition by introducing one pollen‐free foundress, followed 24 h later by seven pollen‐laden ovipositor‐excised wasps. Compared with P+ and P− single‐foundress figs, delayed pollination resulted in intermediate larval mortality and wasp fitness, which concurred with patterns of female offspring production. We conclude that fig abortion reflects both pollinator numbers and pollen presence. Sanctions within P− figs initiate soon after oviposition and discriminate against female offspring, thus reducing the benefits to cheats from adaptively biasing their offspring sex ratios. We suggest that costs to cheats via these discriminative sanctions are likely to promote stability in this mutualism.

The association between the Lys751Gln polymorphism in the XPD gene and the risk of bladder cancer - Tianyuan Xiong; Jiqiao Yang; Haichuan Wang; Fanyi Wu; Yang Liu; Rui Xu; Zi Lv; Pei Xue; Wen Cao; Yonggang Zhang (Molecular Biology Reports, 2014)

Recombinant expression and characterization of an acid-, alkali- and salt-tolerant β-1,3-1,4-glucanase from Paenibacillus sp. S09 - Rui Cheng; Linxiang Xu; Shiming Wang; Yang Wang; Jianfa Zhang (Biotechnology Letters, 2014)

Catastrophe theory to assess water security and adaptation strategy in the context of environmental change - Wang Xiao-jun; Zhang Jian-yun; Shamsuddin Shahid; Xia Xing-hui; He Rui-min; Shang Man-ting (Mitigation and Adaptation Strategies for Global Change, 2014)

Static corrections methods in the processing of deep reflection seismic data - Xiaosan Zhu; Rui Gao; Qiusheng Li; Ye Guan; Zhanwu Lu; Haiyan Wang (Journal of Earth Science, 2014)

Monitoring and modeling the effects of groundwater flow on arsenic transport in Datong Basin - Qian Yu; Yanxin Wang; Rui Ma; Chunli Su; Ya Wu; Junxia Li (Journal of Earth Science, 2014)

Distribution and geologic significance of Girvanella within the Yijianfang Ordovician reef complexes in the Bachu area, West Tarim Basin, China - Hui Rong; Yangquan Jiao; Yongbiao Wang; Liqun Wu; Rui Wang (Facies, 2014)

Assessment of the reproductive toxicity of inhalation exposure to ethyl tertiary butyl ether in male mice with normal, low active and inactive ALDH2 - Zuquan Weng; Katsumi Ohtani; Megumi Suda; Yukie Yanagiba; Toshihiro Kawamoto; Tamie Nakajima; Rui-Sheng Wang (Archives of Toxicology, 2014)

Irregular western margin of the Yangtze block as a cause of variation in tectonic activity along the Longmen Shan fault zone, eastern Tibet - Xiaoyu Guo; G. Randy Keller; Rui Gao; Xiao Xu; Haiyan Wang; Wenhui Li (International Geology Review, 2014)

Two new compounds from a marine-derived fungus Penicillium oxalicum - Pei-Le Wang; Dan-Yi Li; Lei-Rui Xie; Xin Wu; Hui-Ming Hua; Zhan-Lin Li (Natural Product Research, 2014)

Infrared and visible image fusion based on random projection and sparse representation - Rui Wang; Linfeng Du (International Journal of Remote Sensing, 2014)

Pollen morphology and its phylogenetic implications in the genus Picea - Zi Rui Jia; Jun Hui Wang; Shou Gong Zhang (Plant Systematics and Evolution, 2014)

Mechanism and comprehensive countermeasure for drought management from the view of catastrophe theory - Xiao-jun Wang; Jian-yun Zhang; Xue-wei Tong; Shahid Shamsuddin; Rui-min He; Xing-hui Xia (Natural Hazards, 2014)

Synthesis and antitumor activity evaluation of 2-arylisoquinoline-1,3(2H,4H)-diones in vitro and in vivo - Bo-Rui Kang; Juan Wang; Huan Li; Yan Li; Qi-Bing Mei; San-Qi Zhang (Medicinal Chemistry Research, 2014)

Condensation of water vapour on moss-dominated biological soil crust, NW China - XIN-PING WANG; YAN-XIA PAN; RUI HU; YA-FENG ZHANG; HAO ZHANG (Journal of Earth System Science, 2014)

Selection and Characterization of a Peptide Specifically Targeting to Gastric Cancer Cell Line SGC-7901 Using Phage Display - Han Wang; Rui Li; Caixia Ma; Shaoying Lu; Dan Zhang; Yonge Guo; ChunYan Li; Jinling Wu; Qixuan Wang; Jinhui Xu; Yanyan Hu; Yuen Liu; et al. (International Journal of Peptide Research and Therapeutics, 2014)

Isolation, culture, and characterization of primordial germ cells in Mongolian sheep - Chun Xia Liu; Wen Long Wang; Rui Yuan Zhao; Hai Tao Wang; Yi Yi Liu; Shen Yuan Wang; Huan Min Zhou (In Vitro Cellular & Developmental Biology - Animal, 2014)

Next generation sequencing-based molecular diagnosis of retinitis pigmentosa: identification of a novel genotype-phenotype correlation and clinical refinements - Feng Wang; Hui Wang; Han-Fang Tuan; Duy H. Nguyen; Vincent Sun; Vafa Keser; Sara J. Bowne; Lori S. Sullivan; Hongrong Luo; Ling Zhao; Xia Wang; Jacques E. Zaneveld; et al. (Human Genetics, 2014)

An Endophytic Sanguinarine-Producing Fungus from Macleaya cordata, Fusarium proliferatum BLH51 - Xue-Jun Wang; Chang-Li Min; Mei Ge; Rui-Hua Zuo (Current Microbiology, 2014)

Plant diversity as a good indicator of vegetation stability in a typical plateau wetland - Wei Li; Rui Tan; Yu-ming Yang; Juan Wang (Journal of Mountain Science, 2014)

Shapinggou: the largest Climax-type porphyry Mo deposit in China - Hong Zhang; Cong-Ying Li; Xiao-Yong Yang; Ya-Li Sun; Jiang-Hong Deng; Hua-Ying Liang; Rui-Long Wang; Bo-Hua Wang; Yu-Xian Wang; Wei-Dong Sun (International Geology Review, 2014)

Spatial and temporal plasticity of synaptic organization in anterior cingulate cortex following peripheral inflammatory pain: multi-electrode array recordings in rats - Yun-Fei Lu; Yan Wang; Ying He; Fu-Kang Zhang; Ting He; Rui-Rui Wang; Xue-Feng Chen; Fei Yang; Ke-Rui Gong; Jun Chen (Neuroscience Bulletin, 2014)

MicroRNA-128 regulates the differentiation of rat bone mesenchymal stem cells into neuron-like cells by Wnt signaling - Rui Wu; Yue Tang; Wenqiao Zang; Yuanyuan Wang; Min Li; Yuwen Du; Guoqiang Zhao; Yuming Xu (Molecular and Cellular Biochemistry, 2014)

Extent of underthrusting of the Indian plate beneath Tibet controlled the distribution of Miocene porphyry Cu–Mo ± Au deposits - Rui Wang; Jeremy P. Richards; Zengqian Hou; Zhiming Yang (Mineralium Deposita, 2014)

JNK Is Necessary for Oligodendrocyte Precursor Cell Proliferation Induced by the Conditioned Medium from B104 Neuroblastoma Cells - Jing-Xing Zhang; Yi-Fan Feng; Qi Qi; Lin Shen; Rui Wang; Jian-Sheng Zhou; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2014)

Markers associated with altitude and ecological factors in hexaploid Campeiostachys nutans (Griseb.) J. L. Yang, B. R. Baum et C. Yen and tetraploid Roegeneria nutans (Keng) Keng - Yu-Xia Guo; Cheng-Zhang Wang; Xue-Bing Yan; Rui-Yong Wang; Sha-Sha Liu; Miao Tian (Genetic Resources and Crop Evolution, 2014)

Simazine biodegradation and community structures of ammonia-oxidizing microorganisms in bioaugmented soil: impact of ammonia and nitrate nitrogen sources - Rui Wan; Yuyin Yang; Weimin Sun; Zhao Wang; Shuguang Xie (Environmental Science and Pollution Research, 2014)

Effects of bromide and iodide ions on the formation of disinfection by-products during ozonation and subsequent chlorination of water containing biological source matters - Xiao-song Zha; Yan Liu; Xiang Liu; Qiang Zhang; Rui-hua Dai; Ling-wen Ying; Jin Wu; Jing-ting Wang; Luming Ma (Environmental Science and Pollution Research, 2014)

Extracellular DNA Inhibits Salmonella enterica Serovar Typhimurium and S. enterica Serovar Typhi Biofilm Development on Abiotic Surfaces - Hu Wang; Yang Huang; Shuyan Wu; Yuanyuan Li; Ying Ye; Yajie Zheng; Rui Huang (Current Microbiology, 2014)

Identification of a novel fumarase C from Streptomyces lividans TK54 as a good candidate for l-malate production - Rui-Rui Su; Ao Wang; Song-Tao Hou; Peng Gao; Guo-Ping Zhu; Wen Wang (Molecular Biology Reports, 2014)

Cloning and expression patterns of the brine shrimp (Artemia sinica) glycogen phosphorylase (GPase) gene during development and in response to temperature stress - Na Zhao; Ming Hou; Ting Wang; Yifei Chen; Ying Lv; Zengrong Li; Rui Zhang; Wenting Xin; Xiangyang Zou; Lin Hou (Molecular Biology Reports, 2014)

A new algorithm for tight integration of real-time GPS and strong-motion records, demonstrated on simulated, experimental, and real seismic data - Rui Tu; Maorong Ge; Rongjiang Wang; Thomas R. Walter (Journal of Seismology, 2014)

Effects of submerged macrophytes on the abundance and community composition of ammonia-oxidizing prokaryotes in a eutrophic lake - Da-yong Zhao; Juan Luo; Jin Zeng; Meng Wang; Wen-ming Yan; Rui Huang; Qinglong L. Wu (Environmental Science and Pollution Research, 2014)

Climate change and water resources management in Tuwei river basin of Northwest China - Wang Xiao-jun; Zhang Jian-yun; Wang Jian-hua; He Rui-min; Amgad ElMahdi; Liu Jin-hua; Wang Xin-gong; David King; Shamsuddin Shahid (Mitigation and Adaptation Strategies for Global Change, 2014)

Lack of association between the polymorphisms of hypoxia-inducible factor 1A (HIF1A) gene and SLE susceptibility in a Chinese population - Chen-Chen Feng; Qian-Ling Ye; Yan Zhu; Rui-Xue Leng; Gui-Mei Chen; Jie Yang; Han Cen; Xiao-Ke Yang; Rui Li; Wang-Dong Xu; Hai-Feng Pan; Dong-Qing Ye (Immunogenetics, 2014)

The apoptosis of peripheral blood lymphocytes promoted by hyperbaric oxygen treatment contributes to attenuate the severity of early stage acute pancreatitis in rats - Xuewei Bai; Zengfu Song; Yanmei Zhou; Shangha Pan; Feng Wang; Zuoming Guo; Maitao Jiang; Gang Wang; Rui Kong; Bei Sun (Apoptosis, 2014)